The Reality of the Misrata Medical Hospital Library: A Field Study - Abdel Samie, Kholoud Abdel Salam; Al -Naji, Ali Abdul Salam; Aghafir, Nawras Mansour (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study aimed to identify the reality of the Misrata Medical Library, which is one of the specialized libraries that covers many specialized fields and topics in the field of medicine, because it provides sources of information for the specialty it serves, and provides its services to specialized groups of doctors, those interested, students, and researchers in the field of medical sciences. The descriptive analytical approach was used to present and analyze data, through a field study of the library in terms of the building and equipment, the workforce (library workers), information and library services, collections and their organization, holdings, technical procedures, office activities, and the extent of use of information technology and modern technologies. The study used personal interviews, field visits, and a questionnaire as tools to collect information. It designed two questionnaires, one of which was allocated to library employees and the other to beneficiaries of library services, including doctors, students, researchers, and those interested in the field of medical sciences, to arrive at a set of results and a set of recommendations and proposals that would raise the level of the library in question. the study.